S. João de Loure Bridge: vulnerability assessment and study of a common strengthening solution - Varum, H. (2012)
This paper presents a structural vulnerability assessment of the steel bridge S. João de Loure. A structural model of the bridge was created and the influence of the joint’s stiffness on its structural response was evaluated using the structural analysis software SAP2000. Natural frequencies, axial forces and corresponding stress, and maximum mid-span deflection, were analyzed. A common strengthening solution with prestressing cables was studied intending to reduce the bridge’s mid-span deflection.